2018
DOI: 10.21273/hortsci12897-18
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization in Soil Affects Physiological Characteristics and Quality of Green Tea Leaves

Abstract: To study the effects of soil nitrogen (N) fertilization on tea growth, quality and yield, a controlled experiment with green tea [Camellia sinensis (L.) O. Ktze] was conducted. Five N fertilization treatments in soil were designed: 0, 0.97, 1.94, 3.88, and 5.82 g/kg/pot, which were subsequently recorded as N0, N1, N2, N3, and N4. The changes to young shoot biomass, total N and carbon (C), Soil and Plant Analyzer Development (SPAD) value, photosynthetic parameters, senescent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Ma et al (2021) in the Zhejiang province of China also reported a significant increase in the yield of harvested shoots with application of N fertilisers [29], with yields reaching a plateau at an application rate of 367 kg N ha −1 year −1 . In a short-term pot experiment, Xiao et al (2018) reported a yield response of tea up to a level of 3.88 g N (kg soil) −1 [23]. The potential tea yield in a given location is primarily dependent on the climate conditions [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al (2021) in the Zhejiang province of China also reported a significant increase in the yield of harvested shoots with application of N fertilisers [29], with yields reaching a plateau at an application rate of 367 kg N ha −1 year −1 . In a short-term pot experiment, Xiao et al (2018) reported a yield response of tea up to a level of 3.88 g N (kg soil) −1 [23]. The potential tea yield in a given location is primarily dependent on the climate conditions [28].…”
Section: Resultsmentioning
confidence: 99%
“…All units were converted into standard S.I. units with the exception of Xiao et al (2018) for which insufficient data were available [23]. Overall, our approach allowed us to synthesise and identify the need for N, current practices adopted by tea plantations, their impacts, and consequences for the environment, as well as any practices that can help in mitigation highlighted in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Growth-promoting hormones, ZR, IAA, and GA 1+3 are bene cial for plant growth, but their mechanisms are different in different plant organs (Ciura and Kruk 2018). N application was reported to increase ZT content of the leaves of Green tea, while the concentration of ABA, a growth inhibiting hormone, decreased with N application (Xiao et al 2018). The reported differences on the effect of N on hormones in different plant organs may be attributed to differences in plant species and organ types.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the result of studies on the effect endogenous hormones on the allometric growth of plant organs differ considerably. Xiao et al (2018) reported that IAA, GA, and ZT (the same function as ZR) promoted the growth of tea stems and leaves, while ABA inhibited the growth of tea stems and leaves. The content of IAA and ZT increased with root growth, while the content of GA decreased and ABA remained unchanged (Li et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of N fertilizer enriches the formation and accumulation of free amino acids [ 10 , 11 ] while increases or decreases the concentration of polyphenol [ 12 ] in tea shoots. Xiao et al [ 13 ] demonstrated that N incorporation remarkably increased the caffeine concentration, while significantly decreased the concentration of soluble sugars in tea shoots [ 13 ].…”
Section: Introductionmentioning
confidence: 99%